Innovative mnemonics in chemical education a handbook for classroom lectures - Das, Arijit (Cambridge Scholars Publishing, 2019)
This book details formulae-based, time-economic, and innovative learning techniques in chemistry, which serve to help students grow an interest in chemistry, and memorise specific aspects of the subject. It highlights the limitations of conventional methods and solves them in innovative ways. The volume also provides different chemical applications and problems, which will encourage students to solve multiple choice-type questions (MCQs), and highlights some attractive, free educational chemistry tools, which can be used in solving a number of different problems.